Efektifitas Penggunaan Aplikasi Google Classroom Terhadap Motivasi Belajar Mahasiswa PGSD Universitas Muslim Buton - Habibi Musa; Sukmawati Sukmawati; Hartinawanti Hartinawanti (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2021)
The purpose of this study was to determine the effectiveness of the use of the Google Classroom application on the learning motivation of PGSD students at the Muslim University of Buton during the Pandemic. This research is qualitative research. This research was conducted at the Muslim University of Buton. Data collection techniques in this study were interviews, observation and documentation. Interviews were conducted with students and lecturers of PGSD at the Muslim University of Buton. Observations were made by means of researchers making direct observations in the learning process through the google classroom application. The documentation technique in this study was carried out by looking for journals and previous research on E-Learning, mainly about the use of the google classroom application. The research data were then analyzed in 3 ways, namely data reduction, data presentation, and drawing conclusions and verification. To prove the data obtained are truly valid, the researchers used triangulation techniques. The results showed that the Google Classroom application was effectively used and could increase the learning motivation of PGSD students at the Muslim University of Buton during the pandemic.